Tattoo Granulomas With Uveitis - Guiset Carvajal Bedoya MD; Liron Caplan MD, PhD; Karen L. Christopher MD; Amit K. Reddy MD; Cristos Ifantides MD (SAGE Publishing, 2020)
Bilateral intraocular inflammation and simultaneous development of tattoo granulomas has been described in several case reports. The pathophysiology of this process is poorly understood, and it has been hypothesized that it could be a similar mechanism to systemic sarcoidosis versus a delayed hypersensitivity response. Granulomatous tattoo reaction with associated uveitis can manifest with or without evidence of systemic sarcoidosis, and it is usually responsive to immunosuppression and/or tattoo removal. We present a patient with no prior diagnosis of sarcoidosis who developed bilateral panuveitis and tattoo changes suggestive of tattoo granulomas with uveitis (TAGU). The patient was initially managed with intraocular steroids and systemic steroids with minimal improvement of symptoms. The patient later required steroid sparing therapy with a tumor factor inhibitor to achieve remission. There is a growing prevalence of tattooing among the general population and a low reported rate of tattooing complications. Granulomatous tattoo reaction with associated uveitis should be a consideration in patients with tattoos presenting with "idiopathic" uveitis.